Process Analysis of Fragment Penetrating Natural Rubber Material. Issue 1 (August 2021) - Hong, Dou; Li, Wenbin; Zheng, Yu; Jiang, Ning; Pu, Bo
Abstract: The anti penetration characteristics of natural rubber and the influence of fragment velocity on penetration energy were studied. Through the experimental study, the ultimate penetration velocity of different diameter fragments penetrating different thickness rubber target is obtained, and the penetration process is analyzed. The damage characteristics of target are explained through different stages of penetration. At the same time, the influence law of different residual velocity on the expansion velocity of rubber fragment cloud behind target is obtained, the energy required for the fragments to penetrate the target and the expansion velocity of the fragments after the target will increase with the increase of the fragments' entry velocity.